Design and application of a novel 3D printing digital navigation template for cubitus varus deformity in children - Zou, Ming; He, Youzhi; Xu, Yuxia; Shi, Qiang; Zeng, Hao (Frontiers in Pediatrics, 2024)
Background: This present study is aimed to retrospectively explore the feasibility and efficacy of a novel 3D printing digital navigation template for treatment of cubitus varus deformity in children.Methods: 32 consecutive patients with cubitus varus deformity who underwent lateral closing osteotomy were evaluated between January 2018 and January 2020 in this retrospective study. Novel 3D printing digital navigation templates were used in 17 cases, while traditional surgery was used in 15 cases. The carrying angles before and after surgery, operation time and postoperative elbow joint function using Bellemore criteria were compared between the two groups.Results: All 3D printing digital navigation templates matched well with the anatomical markers of the lateral humerus for preoperative planning and intraoperative procedures. Compared with the conventional group, the navigation template group had more accurate osteotomy degrees, less radiation exposure, and shorter operation time (p < 0.05). According to the Bellemore criteria, there was significant difference between the two groups at the last follow-up (p = 0.0288).The novel 3D printing digital navigation template can shorten operation time, improve the lateral closing osteotomy accuracy and improve postoperative elbow joint function for treatment of cubitus varus deformity in children.